Risk Factors of Emergence Agitation in Adults Undergoing General Anesthesia for Nasal Surgery - Kim, Hyo-Jin (Clin Exp Otorhinolaryngol, 2015)
OBJECTIVES: To identify the incidence and the risk factors of emergence agitation in adults undergoing general anesthesia for nasal surgery. METHODS: We retrospectively examined 792 patients aged ≥18 years who underwent general anesthesia for elective nasal surgery between July 2012 and August 2013. Patients in the postanesthesia care unit with a Richmond Agitation Sedation Scale≥+1 at any time were considered to have emergence agitation. RESULTS: The overall incidence of emergence agitation is 22.2%. From multivariate regression analysis, the following six variables were found to be significantly associated with emergence agitation (P<0.05): younger age, recent smoking, sevoflurane anesthesia, postoperative pain on the numerical rating scale (NRS)≥5, presence of a tracheal tube, and presence of a urinary catheter. Presence of a tracheal tube was the greatest risk factor, increasing the risk of developing emergence agitation by approximately fivefold (odds ratio, 5.448; 95% confidence interval, 2.973 to 9.982). Younger age was also a strong risk factor (odds ratio, 0.975 for each 1-year increase; 95% confidence interval, 0.964 to 0.987). Current smoking, sevoflurane anesthesia, postoperative pain of NRS≥5, and the presence of a urinary catheter nearly doubled the risk of emergence agitation. CONCLUSION: Emergence agitation following general anesthesia is a common complication in adult nasal surgery patients. To reduce the occurrence and consequences of agitation episodes, elimination of the associated risk factors is necessary, especially in at-risk patients.